If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 36y = -12graph Solving 4x + 36y = -12aghpr Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36y' to each side of the equation. 4x + 36y + -36y = -12aghpr + -36y Combine like terms: 36y + -36y = 0 4x + 0 = -12aghpr + -36y 4x = -12aghpr + -36y Divide each side by '4'. x = -3aghpr + -9y Simplifying x = -3aghpr + -9y
| 2x+8(x-2)=4x-3(3-2x)-7 | | 3+3x=-7+x | | 6x-3(2x-4)+1=13 | | 15-4x+30=7-x | | 4+12+x=4+6+2x | | -0.01x^2+1.8x-106=0 | | 3+55x=33x+9 | | 4x+7=6x-19 | | (5y+9)+y= | | 11.8-0.4x+3.6=40 | | 25-2(4x+15)=51 | | -13+2x=-39+24x | | 25.00(x+5.00)=425.00 | | 5000=150+400 | | 32-3x=11-2x | | 10+3x=-6x-98 | | 3x^2+8x-91=0 | | 3(x+4)-5x=72 | | 65+900+b=1053 | | 5.87b=8.68+3.68b | | (19-X)-(18-X)=3 | | 16=4(x-2) | | n^2-10n-88=8 | | 3(5-x)=2(1+x) | | 6y=5x+60 | | 4x^2-17x+34=6x+6 | | 2n^2+5n-33=12 | | 19x-18x=3 | | x+3x+3x+5=166 | | 3(m+4)=-24-m | | 10-2x=20x+4 | | log(x-11)+log(x-8)=1 |